Global and regional trends in greenhouse gas emissions from rice production, trade, and consumption - Wang, Xiang; Chang, Xiaoyan; Ma, Libang; Bai, Jing; Liang, Man; Yan, Simin (Environmental impact assessment review, 2023)
As the content of the climate policy to meet the 2 °C targets, actions in all economic sectors, including agriculture, are required to mitigate global greenhouse gas (GHG) emissions. Although there has been an ever-increasing focus on agricultural GHG emissions, little is known about the environmental benefits of individual crops, making it challenging to link production to consumption (including trade) and GHG emissions. In this study, we estimated GHG emissions related to rice in 227 countries and three sectors, taking time series data from the Food and Agriculture Organization (FAO) from 1986 to 2017. The results showed that production-based emissions increased by 25.5%, and actual consumption-based presented the same trend while assuming domestic production (no trade) expanded by 45.1%. The reason for the unbalance between the two sectors is that the total transfer volume embodied in the rice trade increased by 151.6% in 32 years. Meanwhile, we found that trade flows increased from low- to high-emission intensity countries, while rice emissions intensity was significantly reduced, contributing to a global GHG emission reduction of an average of 56.3Mt per year. Our results provide a comprehensive, forward-looking assessment of the environmental impacts of global growing rice production and consumption on the main countries and their trading relationships. Thus, besides domestic policies, main importing countries should also consider environmental benefits in developing sustainable international trade to limit the negative environmental impacts of its growing rice consumption.
Gesehen am 24.07.2023